2005
DOI: 10.1038/sj.emboj.7600444
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin–protein ligase Itch regulates p73 stability

Abstract: p73, a member of the p53 family of transcription factors, is upregulated in response to DNA damage, inducing cell cycle arrest and apoptosis. Besides indications that this p73 response is post‐transcriptional, little is known about the underlying molecular mechanisms of p73 protein degradation. Ubiquitination and proteasomal‐dependent degradation of p53 are regulated by its transcriptional target MDM2. However, unlike p53, p73 binds to, but is not degraded by, MDM2. Here we describe the binding of p73 to Itch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
302
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(315 citation statements)
references
References 50 publications
11
302
0
2
Order By: Relevance
“…One hypothesis is that p73 protein stability is affected by the SAP deficiency. This hypothesis is supported by recent studies on the E3 ubiquitin ligase, Itch, which has been shown to be essential in the regulation of p73 protein stability and transcription, and itself is negatively regulated through FynT-mediated tyrosine phosphorylation at Tyr321 [45,46]. Thus, the decreased FynT activation in the absence of SAP might exert less negative regulation on Itch function, which targets increased ubiquitination and subsequent degradation of p73.…”
Section: Discussionmentioning
confidence: 72%
“…One hypothesis is that p73 protein stability is affected by the SAP deficiency. This hypothesis is supported by recent studies on the E3 ubiquitin ligase, Itch, which has been shown to be essential in the regulation of p73 protein stability and transcription, and itself is negatively regulated through FynT-mediated tyrosine phosphorylation at Tyr321 [45,46]. Thus, the decreased FynT activation in the absence of SAP might exert less negative regulation on Itch function, which targets increased ubiquitination and subsequent degradation of p73.…”
Section: Discussionmentioning
confidence: 72%
“…The polyproline region of p73 that is recognized by Pin1 does in fact overlap with the binding site for YAP, an essential factor directing p73 towards proapoptotic promoters. 74 Intriguingly, conformational alteration of this domain would be expected to interfere with binding of the ubiquitin ligase Itch, 75 thus providing a mechanistic explanation for the observed role of Pin1 in p73 stabilization. 68 Given the similar effects exerted on p53 and p73, Pin1 may well represent a common mediator for cooperative activity among the p53 family members.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%
“…Under normal physiological conditions p73 is degraded either by calpains or by the 26S or 20S proteasomes (Asher et al, 2005;Munarriz et al, 2005;Rossi et al, 2005). While inhibition of calpains increases the steady-state levels of p73 , the E3 ubiquitin ligase Itch promotes 26S proteasome-dependent p73 degradation .…”
Section: Introductionmentioning
confidence: 99%
“…After DNA damage, TAp73 rapidly accumulates (Agami et al, 1999;Gong et al, 1999) predominantly via transcription-independent mechanisms. Indeed, the major determinants regulating p73 accumulation are tyrosine phosphorylation by c-abl, acetylation by p300 and Itch downregulation (Costanzo et al, 2002;Bernassola et al, 2004;Mantovani et al, 2004;Rossi et al, 2005). Once accumulated, TAp73 transactivates genes like p21, Bax and Puma to induce cell cycle arrest or apoptosis (see Melino et al, 2002 for a review).…”
Section: Introductionmentioning
confidence: 99%